Review on environmental aspects in smart city concept: Water, waste, air pollution and transportation smart applications using IoT techniques - Salman, Meric Yilmaz; Hasar, Halil (Elsevier, 2023)
Increasing urban populations due to factors such as more comfortable life and immigration have turned selfsufficient traditional cities into mega-cities and caused several new environmental problems in cities. These problems cannot be solved with the traditional urban understanding as not meet the needs of modern people. Solving the main problems encountered in cities with science and technology approach brings us the concept of smart city. Today, it has become inevitable to offer citizen-oriented solutions to urban problems in order to ensure a sustainable environment for high level of welfare/public health and to manage the effective and correct use of resources. In this review, environmental problems that can be encountered in any city are classified under four main headings as water, waste, air and traffic, and approaches that can be applied in smart city management for the solution of these problems encountered in traditional cities are emphasized in the light of studies in literature, by considering the main environmental problems encountered in cities. Thus, smart methods based solutions are presented against basic problems such as water/wastewater management, waste management, air pollution control and effective transportation encountered in a city.
Keywords: Smart city; water management; waste management; smart solutions; smart applications; smart transportation